Correlation between body condition change and reproduction parameters of Holstein-Frisian cows after calving - M. J. Jónás, Edit; Mucsi, Imre; Komlósi, István (Acta Agraria Debreceniensis, 2010)
The authors examined the body condition with relation to reproduction of Holstein-Friesian cows on three dairy farms in the South Plain region. During the examination they analyzed the data of 516 births of 494 Holstein-Friesian cows. They were trying to find correlation between the first service, the service period and the service rates. The examinations with regard to the correlations were different from the ones published in the professional literature. The body condition at the time of calving affected the interval from calving to the first service but not the conceptionrates or the service period. The examinations did not prove any correlations between body condition changes and reproduction.